2004
DOI: 10.1111/j.1551-2916.2004.00633.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Y2O3 Content and Temperature on the Mechanical Properties of Melt‐Grown Al2O3–ZrO2 Eutectics

Abstract: The effect of Y2O3 content on the flexure strength of melt‐grown Al2O3–ZrO2 eutectics was studied in a temperature range of 25°–1427°C. The processing conditions were carefully controlled to obtain a constant microstructure independent of Y2O3 content. The rod microstructure was made up of alternating bands of fine and coarse dispersions of irregular ZrO2 platelets oriented along the growth axis and embedded in the continuous Al2O3 matrix. The highest flexure strength at ambient temperature was found in the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
6

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 23 publications
(21 reference statements)
2
56
0
6
Order By: Relevance
“…Furthermore, the measured value for these conditions is the highest value obtained for all the samples in all the conditions. It is an excellent result, exceeding about 50% the highest values reported in the literature (7,9).…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…Furthermore, the measured value for these conditions is the highest value obtained for all the samples in all the conditions. It is an excellent result, exceeding about 50% the highest values reported in the literature (7,9).…”
Section: Resultssupporting
confidence: 53%
“…Relationships between growth parameters and Y 2 O 3 amount have been deduced, and it has been demonstrated that care must be carried out to avoid the presence of defects. The most common defects are pores and bands (7,8), which lead to poor mechanical characteristics. From the mechanical point of view, the optimal Y 2 O 3 amount has been established in 3 mol % with respect to ZrO 2 , while the optimal growth velocity has been established in v < 50 mm/h.…”
Section: Introductionmentioning
confidence: 99%
“…En los últimos años se ha vuelto la mirada hacia los óxidos cerámicos eutécticos, procesados por solidificación direccional, que constituyen una nueva familia de materiales con una resistencia mecánica superior a alta temperatura y una gran estabilidad térmica (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Estos materiales, al tener la composición eutéctica, solidifican como compuestos in-situ con una microestructura ordenada que puede variar desde organizaciones fibrosas o laminares a estructuras de colonias o redes interpenetradas.…”
Section: Introductionunclassified
“…Estas barras se colocaron dentro de la cámara de crecimiento y se fundieron localmente con la radiación de un láser de CO 2 . La zona fundida se desplazó a lo largo de la barra permitiendo la solidificación direccional siguiendo el método descrito anteriormente [10]. Con objeto de obtener barras cerámicas con diámetros comprendidos entre 1.2 y 1.6 mm, el crecimiento se llevó a cabo en varias etapas incluyendo sucesivas pasadas de reducción de diámetro.…”
Section: -Procesadounclassified
“…Sin embargo, la existencia de fuertes tensiones residuales de compresión en los granos de Al 2 O 3 incrementó la resistencia a fractura. Una investigación previa de los mecanismos de rotura de este eutéctico [10] mostró que dos (o más) grietas paralelas a menudo se nucleaban a partir de las esquinas de las indentaciones Vickers. Estas grietas crecían una determinada distancia hasta que una de ellas se hacía dominante y el resto se paraban en los granos de Al 2 O 3 .…”
Section: Propiedades Mecánicasunclassified